2019
DOI: 10.1007/jhep10(2019)050
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter in the Randall-Sundrum model with non-universal coupling

Abstract: We consider simplified dark matter models (DM) interacting gravitationally with the standard model (SM) particles in a Randall-Sundrum (RS) framework. In this framework, the DM particles interact through the exchange of spin-2 Kaluza-Klein (KK) gravitons in the s-channel with the SM particles. The parameter space of the RS model with universal couplings to SM particles is known to be strongly constrained from the LHC data. We are thus led to consider models with non-universal couplings. The first model we cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…These extra-dimensional models are being probed by the LHC [8], where we can search for TeV scale KK excitations as a signature of physics beyond the Standard Model. Extra-dimensional theories that additionally incorporate neutral stable matter motivate certain dark matter models, where particulate dark matter interacts with the Standard Model through a massive spin-2 mediator (see, for example, [9][10][11][12][13][14][15]). 1 The extra-dimensional gravitational action in these models gives rise to interactions between the massive spin-2 KK resonances.…”
Section: Introductionmentioning
confidence: 99%
“…These extra-dimensional models are being probed by the LHC [8], where we can search for TeV scale KK excitations as a signature of physics beyond the Standard Model. Extra-dimensional theories that additionally incorporate neutral stable matter motivate certain dark matter models, where particulate dark matter interacts with the Standard Model through a massive spin-2 mediator (see, for example, [9][10][11][12][13][14][15]). 1 The extra-dimensional gravitational action in these models gives rise to interactions between the massive spin-2 KK resonances.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [8], we have demonstrated that the muon g − 2 anomaly can be explained by the one-loop effects induced by a new spin-2 particle G, which can be identified as the first Kaluza-Klein (KK) graviton in the generalized Randall-Sundrum (RS) model [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. By calculating all relevant one-loop Feynman diagrams, we have obtained the analytic expression of the leading-order G-induced contribution to the muon g − 2, which is shown to maintain both the gauge invariance of the quantum electrodynamics and the correct divergence structure of loop integrals.…”
Section: Introductionmentioning
confidence: 99%
“…Gravity-mediated DM WIMP's (i.e., stable or cosmologically long-lived weakly interactive massive particle, with mass typically in the range 100-1000 GeV, and whose relic abundance is set via the freeze-out mechanism) have been studied mainly in the framework of the RS scenario [12][13][14][15][16][17][18][19][20][21], with generic spin-2 mediators [22][23][24][25] and in the context of the CW/LD model [26].…”
Section: Introductionmentioning
confidence: 99%